PENDAMPINGAN PSIKOSOSIAL DAN MODUL PEMBELAJARAN SEKOLAH DASAR UNTUK MENGATASI LEARNING LOSS - Mufarrihul Hazin; Syarif Hidayat; Agus Suherman Tanjung; Ahmad Syamwiel; Abdul Hakim (LPPM Universitas Bina Bangsa, 2021)
Covid-19 has made significant changes in the education world, especially in the process of teaching and learning activities, a result of curriculum changes and the compaction of learning materials, the potential of children, especially those in disadvantaged, frontier, and outermost (3T) areas of Indonesia Might lose their right to learn, this causes learning loss. This program aims to help elementary school students in 3T and non 3T areas to get good education quality rights during the Covid-19 Pandemic. The method used in the mentoring model is PAR (Participatory Action Research). The target of this assistance consists of 5 schools in Musi Rawas Utara, SDN 1 Maur, SDN 3 Maur, SDN Batu Gajah, SDN Bingin Rupit Ulu, SDN Tanjung Beringin. The results of the mentoring of this Program are; 1) Initial assessment related to learning difficulties during Covid-19 and the models and strategies used by teachers in the process of teaching and learning activities, 2) Implementation of psychosocial assistance for teachers, students, and parents through home visits and invitations to schools 2) Assisting learning modules in the form of two components, namely the literacy and numeracy modules, activities in the form of assistance to teachers, parents and students throughout learning activities at school and visits to parents and students.